Femi and His Dog - Olanlokun, Olajire (Pearson Education Ltd, 2004)
This is the story of named Femi who got a dog as a birthday gift and really love the dog. But his sister who didn't like the dog,but she started to like the dog when the dog gave birth to puppies that where sold and the money was used to buy a much desired bicycle for her.
Keywords: Juvenile literature-Fiction-Nigeria (English)